The Modified Decomposition Method for Solving A Nonlinear System of Two-dimensional Volterra-Fredholm Integral Equation - Abd Rahman, Salmiah; Mohamad, Mahathir; Md Shab, Noorzehan Fazahiyah (Enhanced Knowledge in Sciences and Technology, 2021)
In this study, Modified Decomposition Method (MDM) was used to solve the nonlinear system of two-dimensional Volterra-Fredholm integral equations. The solution of the approximate equation is calculated with the help of Maple software. This method is proved to reduce computational works and simple to apply. The numerical results obtained in MDM are compared with the exact solution to see the accuracy of the method. A comparison of the absolute errors between MDM and Successive Iterative Method shows that MDM is more efficient than other methods.